Evolutionary map of the Universe (EMU): Compact radio sources in the scorpio field towards the galactic plane. Issue 1 (8th January 2021) - Riggi, S; Umana, G; Trigilio, C; Cavallaro, F; Ingallinera, A; Leto, P; Bufano, F; Norris, R P; Hopkins, A M; Filipović, M D; Andernach, H; van Loon, J Th; et al.
ABSTRACT: We present observations of a region of the Galactic plane taken during the Early Science Program of the Australian Square Kilometre Array Pathfinder (ASKAP). In this context, we observed the scorpio field at 912 MHz with an uncompleted array consisting of 15 commissioned antennas. The resulting map covers a square region of ∼40 deg 2, centred on ( l, b ) = (343.5°, 0.75°), with a synthesized beam of 24 × 21 arcsec 2 and a background rms noise of 150–200 μ Jy beam −1, increasing to 500–600 μ Jy beam −1 close to the Galactic plane. A total of 3963 radio sources were detected and characterized in the field using the caesar source finder. We obtained differential source counts in agreement with previously published data after correction for source extraction and characterization uncertainties, estimated from simulated data. The ASKAP positional and flux density scale accuracy were also investigated through comparison with previous surveys (MGPS, NVSS) and additional observations of the scorpio field, carried out with ATCA at 2.1 GHz and 10 arcsec spatial resolution. These allowed us to obtain a measurement of the spectral index for a subset of the catalogued sources and an estimated fraction of (at least) 8 per cent of resolved sources in the reported catalogue. We cross-matched our catalogued sources with different astronomical data bases to search for possible counterparts, finding ∼150 associations to known Galactic objects. Finally, we explored a multiparametric approach for classifying previously unreported Galactic sources based on their radio-infrared colours.